"I see you, I know you, it feels good" – Qualitative and quantitative analyses of ambient awareness as a potential mediator of social networking sites usage and well-being. (December 2017) - Krämer, Nicole C.; Neubaum, German; Hirt, Melanie; Knitter, Carina; Ostendorf, Sina; Zeru, Sewit
Abstract: Ambient awareness describes a new form of peripheral social awareness which relates to the omnipresent knowledge about friends or acquaintances, resulting from continuous contact without active communication. We examined possible relations between intensity of social networking site usage, ambient awareness, social connectedness, and well-being. We conducted an exploratory interview study ( N  = 14) as well as an online survey ( N  = 235). Results indicated that the concept resonated with participants and that they experience both positive as well as negative aspects of ambient awareness. Quantitative data showed positive relations between intensity of Facebook usage and ambient awareness as well as between ambient awareness and increased well-being. Social connectedness moderates the relation in the sense that ambient awareness may be psychologically beneficial especially for those who generally have a low social connectedness. Highlights: Intensity of Facebook usage is positively related to the feeling of ambient awareness (i.e. peripheral social awareness). Ambient awareness is positively related to well-being. Ambient awareness is beneficial especially for those who do not feel socially connected.